Axon Guidance-Related Factor FLRT3 Regulates VEGF-Signaling and Endothelial Cell Function - Jauhiainen, Suvi; Laakkonen, Johanna P.; Ketola, Kirsi; Toivanen, Pyry I.; Nieminen, Tiina; Ninchoji, Takeshi; Levonen, Anna-Liisa; Kaikkonen, Minna U.; Ylä-Herttuala, Seppo (Frontiers in Physiology, 2019)
Vascular endothelial growth factors (VEGFs) are key mediators of endothelial cell (EC) function in angiogenesis. Emerging knowledge also supports the involvement of axon guidance-related factors in the regulation of angiogenesis and vascular patterning. In the current study, we demonstrate that fibronectin and leucine-rich transmembrane protein-3 (FLRT3), an axon guidance-related factor connected to the regulation of neuronal cell outgrowth and morphogenesis but not to VEGF-signaling, was upregulated in ECs after VEGF binding to VEGFR2. We found that FLRT3 exhibited a transcriptionally paused phenotype in non-stimulated human umbilical vein ECs. After VEGF-stimulation its nascent RNA and mRNA-levels were rapidly upregulated suggesting that the regulation of FLRT3 expression is mainly occurring at the level of transcriptional elongation. Blockage of FLRT3 by siRNA decreased survival of ECs and their arrangement into capillary-like structures but enhanced cell migration and wound closure in wound healing assay. Bifunctional role of FLRT3 in repulsive vs adhesive cell signaling has been already detected during embryogenesis and neuronal growth, and depends on its interactions either with UNC5B or another FLRT3 expressed by adjacent cells. In conclusion, our findings demonstrate that besides regulating neuronal cell outgrowth and morphogenesis, FLRT3 has a novel role in ECs via regulating VEGF-stimulated EC-survival, migration and tube formation. Thus, FLRT3 becomes a new member of the axon guidance-related factors which participate in the VEGF-signaling and regulation of the EC functions.